Sacubitril/valsartan: research progress of multi-channel therapy for cardiorenal syndrome - Wang, Shuangcui; Wang, Yuli; Deng, Yun; Zhang, Jiaqi; Jiang, Xijuan; Yu, Jianchun; Gan, Jiali; Zeng, Wenyun; Guo, Maojuan (Frontiers in Pharmacology, 2023)
Cardiorenal syndrome (CRS) results from complex interaction between heart and kidneys, inducing simultaneous acute or chronic dysfunction of these organs. Although its incidence rate is increasing with higher mortality in patients, effective clinical treatment drugs are currently not available. The literature suggests that renin-angiotensin-aldosterone system (RAAS) and diuretic natriuretic peptide (NPs) system run through CRS.Drugs only targeting the RAAS and NPs systems are not effective. Sacubitril/valsartan contains two agents (sacubitril and valsartan) that can regulate RAAS and NPs simultaneously. In the 2017 American College of Cardiology/American Heart Association/American Heart Failure Association (ACC/AHA/HFSA) guideline, sacubitril/valsartan was recommended as standard therapy for heart failure patients. However, fewer studies have reported its therapeutic efficacy in CRS treatment, and their results are inconclusive. Therefore, based on RAAS and NPs as CRS biomarkers, this paper summarizes possible pathophysiological mechanisms and preliminary clinical application effects of sacubitril/valsartan in the prevention and treatment of CRS. This will provide a pharmacological justification for expanding sacubitril/valsartan use to the treatment of CRS.